School Principal's Efforts as an Innovator in Improving Performance at Madrasah Ibtidaiyah - Mufron, Ali; Yusrianti, Susi; Irfana, Tungga Buana; Firdausiyah, Luluk; Kurniawan, Andri (Al-Hijr: Journal of Adulearn World, 2024)
In essence, the principal has the responsibility to improve the work program. In its development, not all aspects are in accordance with what is expected. Principals must have good performance experience in improving the innovations that will be developed. This research aims to find out efforts to improve performance with various innovations made by school principals. Thus, this research uses quantitative methods by conducting an in-depth review through the use of whatsApp applications. The results that researchers get from the research conducted are researchers can find out what innovations are made by school principals to improve the performance of Madrasah Ibtidaiyah for students. From the research conducted by the researcher, it can be concluded that, the efforts of innovation made by the principal to improve performance are good, but it is hoped that a review will be carried out to the government in order to maximize the performance expected by the principal of the teachers, students in the school, because if seen at this time the principal only gets information from each homeroom teacher, by conducting the review, the principal will know what is needed or needed by the school to make the school even superior. The limitation of this research is that researchers do not make a detailed description of what innovations will be made by the head of Madrasah Ibtidaiyah to measure existing progress, therefore further researchers can conduct more detailed research. In order to obtain more maximum innovation or new movements.